Estudo da citotoxicidade e biointerface de nanopartículas de dióxido de titânio utilizadas nas indústrias de cosméticos - Sanches, Priscila Laviola (2017)
The development of the nanotechnology area, in particular in whatregards the production of nanomaterials, is growing exponentially. Human exposure to nanoparticles is high and originated from a variety of sources, such as chemical processes, medical devices (implants, prostheses, controlled drug delivery systems), food, pharmaceutical and cosmetic industries. However, the study of the cytotoxicity of these nanomaterials is contradictory. Therefore, it is extremely important to develop research that analyzes the impact of nanoparticles on human health, as well as generating regulations that up to now is insufficient. Currently, the sunscreens have in their composition nanoparticles such as those of titanium dioxide (TiO2).The use of TiO2 in sunscreen formulation is due to its ability to reflect and spread UVB (290-320 nm) and UVA (320-400 nm) rays ensuring good protection against solar radiation. Therefore, this work aimed to evaluate the potential cytotoxicity of TiO2 nanoparticles in the rutile crystalline structure in human skin cells. Due to the agglomeration of nanoparticles, a nanoparticle dispersion protocol was optimized, first in water and then in biological medium using an indirect sonicator. The dispersion was then characterized by dynamic light scattering (DLS) and electronic transmission microscopy (MET). A study of ions and proteins adsorption was carried out by energy dispersivex-ray spectroscopy (EDS) and mass spectrometry, respectively. We performed an evaluation of the nanoparticles cytotoxic profile in primary cultures of fibroblasts and keratinocytes by the neutral red assay and by flow cytometry. MET allowed the study of the nanoparticles internalization inside cells. The results demonstrate the formation of a bio-complex around nanoparticles surfaces due to the selective adsorption of ions and proteins from the culture medium, such as calcium and phosphorus ions and proteins as albumin, fibronectin and thrombospondin. We observed that human keratinocytes and fibroblasts internalized the nanoparticles, which located in microvesicles that migrate preferentially to the perinuclear region. However, after nanoparticle internalization, there was a significant increase in cell death due to apoptosis and a significant reduction in cell viability in the fibroblasts, as well as increased apoptosis death and necrosis in keratinocytes. We suggest that the bio-complex formation can mask the nanoparticles and modulate their penetration into human skin cells.